2014
DOI: 10.1371/journal.pone.0101794
|View full text |Cite
|
Sign up to set email alerts
|

Protein C Inhibitor (PCI) Binds to Phosphatidylserine Exposing Cells with Implications in the Phagocytosis of Apoptotic Cells and Activated Platelets

Abstract: Protein C Inhibitor (PCI) is a secreted serine protease inhibitor, belonging to the family of serpins. In addition to activated protein C PCI inactivates several other proteases of the coagulation and fibrinolytic systems, suggesting a regulatory role in hemostasis. Glycosaminoglycans and certain negatively charged phospholipids, like phosphatidylserine, bind to PCI and modulate its activity. Phosphatidylerine (PS) is exposed on the surface of apoptotic cells and known as a phagocytosis marker. We hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Plasma-derived MPs of healthy individuals did not bind any exogenously added pPCI-Cy3 as determined by flow cytometry. As positive control we studied the binding of pPCI-Cy3 to apoptotic Jurkat cells known to bind pPCI-Cy3 [ 45 ]. In contrast to MPs from healthy individuals, about 20% of apoptotic Jurkat cells bound pPCI-Cy3 ( Fig 2D ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Plasma-derived MPs of healthy individuals did not bind any exogenously added pPCI-Cy3 as determined by flow cytometry. As positive control we studied the binding of pPCI-Cy3 to apoptotic Jurkat cells known to bind pPCI-Cy3 [ 45 ]. In contrast to MPs from healthy individuals, about 20% of apoptotic Jurkat cells bound pPCI-Cy3 ( Fig 2D ).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies we have shown that annexin V and PCI were co-localized in atherosclerotic plaques [ 41 ]. Furthermore, binding of PCI and annexin V occurred at the same sites on apoptotic Jurkat cells and U937 cells [ 45 ]. The presence of PCI on annexin V binding MPs is therefore an additional indication that PCI and PS interact in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations